english English - Suharto, Suharto (JERAM, 2017)
The purpose of this study was to determine the effect supervision, school culture, and work commitment of job performance elementary school principal of administrative region II city west Jakarta. This research tried to answer problems about job performance with evidence increasing of service employee. The research was conducted on job performance employee involving of 110 elementary school principal had been selected from the target populations of 128 employees by using the quantitative approach with path analysis methods. The research of hypothesis testing show: (1) supervision had a direct effect positive on job performance; (2) school culture had a direct effect positive on job performance; (3) work commitment had a direct effect positive on job performance; (4) supervision had a direct effect positive on work commitment: (5) school culture had a direct effect positive on work commitment;. Therefore to improve the job performance school principal of administrative region II city west Jakarta. Need to increase supervision, school culture, and work commitment.